Sinisan Protects Primary Hippocampal Neurons Against Corticosterone by Inhibiting Autophagy via the PI3K/Akt/mTOR Pathway - Zhang, Mingjia; Zhang, Yi; Sun, Haitao; Ni, Hui; Sun, Jialing; Yang, Xuemei; Chen, Weicong; Zhao, Wenting; Zhong, Xiaodan; He, Chunyu; Ao, Haiqing; He, Songqi (Frontiers in Psychiatry, 2021)
Objective: Corticosterone causes significant neurotoxicity in primary hippoc ampal neurons which is associated with depression. Dysfunctional autophagy is implicated in cognitive impairment and depressive-like behavior. The traditional Chinese medicine Sinisan (SNS) is highly effective in clinical treatment of depression. However, the molecular mechanisms underlying therapeutic effects of SNS are unknown. Purpose: The aim of this study was to elucidate the protective effect of SNS and the underlying mechanisms against corticosterone-induced neuronal damage. Study Design: The effects of serum derived from rats containing SNS (or untreated controls) on the expression of autophagy-related molecules in primary rat hippocampal neurons exposed to different concentrations of cortisone corticosterone for different intervals were explored. Methods: CCK-8 assay , LDH assay were used to analyze cell viability and LDH activity. Western blot, qRT-PCR, and immunofluorescence assays were used to determine protein and mRNA expression levels of molecules such as LC3, p62, Beclin1, ULK1, PI3K, p-PI3K, Akt p-Akt, mTOR, p-mTOR, p70S6, p-p70S6, 4ebp1 and p-4ebp1. Results: Corticosterone induced a dose- and time-dependent reduction in cellular viability. Moreover, corticosterone (100–400 M) treatment for 24 h increased LC3-II/LC3-I ratio, increased Beclin1 and ULK1 protein expression levels, and decreased p62, PI3K, p-PI3K, p-Akt, p-mTOR, p-p70S6, and p-4ebp1 protein expression levels. Notably, SNS-containing serum reversed corticosterone-induced reduction of neuronal viability, and increased p62, PI3K, p-Akt, p-mTOR, p-p70S6, and p-4ebp1 protein and mRNA expression levels. In addition, SNS-containing serum decreased LC3-II/LC3-I ratio, and downregulated Beclin1, and ULK1 protein and mRNA expression in primary hippocampal neurons. Conclusion: SNS protects primary hippocampal neurons against corticosterone-induced neurotoxicity by preventing excessive autophagy through activation of PI3K/AKT/mTOR pathway.